MASCULINITIES IN DISPUTE: QUEER PERSPECTIVES TO PARTNERED DANCE EDUCATION AND POLITICS OF EMBODIMENT - Marques, João; Longstaff, Gareth (Diversidade e Educação, 2025)
This article examines how masculinities are produced, negotiated, and contested in educational settings of partnered dance. Drawing on interviews with researchers, teachers, and practitioners from Brazil and abroad, it investigates how embodiment, desire, and intimacy intersect with gendered and sexualized norms embedded in the practice. Guided by queer epistemologies and pedagogies, the study employs a qualitative approach, analyzing narratives to understand the ontological dimensions of dance for two and the interbodily dynamics that shape identities. The findings reveal that representations of masculinities emerge in constant tension between tradition and innovation, local culture and global flows, disciplinary technique and personal expression. These tensions, rather than being obstacles, open possibilities for reimagining partnered dance as an inclusive and reflexive space. The article concludes that such practices can challenge fixed gender norms, fostering more plural, relational, and transformative ways of embodying masculinities.